Effectiveness of water extract of mangrove fruit flour (Rhizophora mucronata) as a natural preservative in skipjack fish fillets (Katsuwonus pelamis) - Maulanan, Risky S; Mile, Lukman; Djailani, Fernandy M. (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Gorontalo is quite potential for the development of capture fisheries potential including the development of skipjack (Katsuwonus pelamis) production. In its processing, natural additives containing antimicrobial compounds are needed to preserve the fish. Rhizophora mucronata or R. mucronata is one type of mangrove that is widely spread along the tourist location